INSTAGRAM SEBAGAI MEDIA DAKWAH (STUDI KASUS INSTAGRAM @PEMUDAHIJRAH) - Aliffiani Ayu Nurrohmah; Ahmad Nurcholis (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2021)
Abstract Preachers nowadays have used social media (social media) to spread their da'wah. The Pemuda Hijrah Instagram account is an account that spreads da'wah content by making videos about da'wah, providing Islamic studies with the theme of inviting young people to emigrate and improve themselves. With the title "Instagram as a Media of Da'wah" the researcher wants to try to use theoretical social learning in order to find out what the target of Instagram is as a medium of da'wah on the Instagram of the hijrah youth. This study uses qualitative research methods by interviewing, observing six followers on the youth hijrah accounts, and also researchers viewing videos on the hijrah youth instagram accounts at least five to ten times for one week. This paper shows that the da'wah strategy can use social media in disseminating video content through the Pemuda Hijrah Instagram account which is considered very efficient in increasing understanding of Islam, increasing optimism, providing motivation, and encouraging behavioral change towards respondents to become more personal good. Keyword: Instagram, Media, Da’wah.